Peningkatan Keterampilan Motorik Kasar Melalui Alat Permainan Simpai pada Anak Kelompok A di Taman Kanak-Kanak Dharma Wanita Bangun Ungging Mojokerto - Amilatul Zahroh; Yahya Aziz; Al Qudus Nofiandri Eko Sucipto Dwijo (JECED : Journal of Early Childhood Education and Development, 2019)
The background of this research is that gross motoric activities in schools are rarely carried out due to the limited facilities and infrastructure owned by the school. The solution to overcome this problem is the application of the hoop game tool. This study aims to determine the application of hulahoop playing tools as an effort to increase gross motor skills in group A children at Dharma Wanita Kindergarten Bangun Pungging Mojokerto. The formulation of the problem in this study include: 1) How to apply the hoop game tool to improve gross motor skills in group A children in Dharma Wanita Kindergarten Bangun Pungging Mojokerto? 2) How to increase gross motor skills through hoop playing tools in group A children at Dharma Wanita Kindergarten Bangun Pungging Mojokerto? This type of research is classroom action research which aims to improve the quality of learning by using the Kemmis & Taggart spiral model action research. The study was conducted in two cycles. Each cycle is held for three meetings. Each cycle consists of four stages: the planning, implementation, observation and reflection stages. The subjects in this study were children of group A totaling 17 students consisting of 8 male students and 9 female students. Data collection techniques used in this study are interviews, observation and documentation. The results of the study can be explained as follows: 1) the application of the hoop game runs well in Cycle II. This can be seen in the results of observations of teacher activities in Cycle I, namely 80 (good) and in Cycle II it increased to 86.66 (very good). The results of observation of student activities in Cycle I were 75 (good) and in Cycle II it rose to 88.33 (very good). 2) increase in gross motor skills based on the average grade of the 59.70 (sufficient) pre cycle, in the cycle up to 69.70 (enough) and in Cycle II it increased to 91.47 (very good). Whereas gross motor percentage at pre cycle was 23.52% (Undeveloped), in Cycle I it was 52.94% (Start developing) and in Cycle II it increased significantly to 88.23% (Developing Very Good).